Pengaruh Organizational Learning Dan Personality Dimediasi Oleh Self Efficacy Terhadap Employee Engagement - Annisa Putri; Ari Anggarani W.P.T (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
This study aims to examine and examine the effect of Organizational Learning and Personality Mediated by Self Efficacy on Employee Engagement at PT. Puninar UMK. Organizational Learning and Personality as exogenous variables, Self Efficacy as mediating variables and Employee Engagement as endogenous variables. This research was conducted on employees of PT. Puninar MSE. The background of this research is the development of human resources which aims to improve the quality of professionalism and skills of employees in carrying out their duties and optimally. Things that must be considered at PT. Puninar MSE such as Organizational Learning, Personality, Self Efficacy and Employee Engagement. The sample in this study was taken by the Non Probability Sampling method using a saturated sample technique of 64 respondents. The analytical method used is the Structural Equation Model (SEM) and uses Partial Least Square (PLS) to test the strength of direct and indirect relationships between various variables. The results of this study prove that Organizational Learning has an effect on Employee Engagement, Personality has an effect on Employee Engagement, Self Efficacy has an effect on Employee Engagement, Organizational Learning has an effect on Self Efficacy, Personality has an effect on Self Efficacy, Organizational Learning has an effect on Employee Engagement through Self Efficacy and Personality has an effect towards Employee Engagement through Self Efficacy.